Análise térmica e energética de briquetes de capim braquiária - Pessoa Filho, José Silvio (2013)
Biomass is one of the main sources of renewable and sustainable energy able to meet the growing global energy demand and reduce dependence on fossil fuels. However, the use of this biofuel requires a conscious and careful handling of natural resources, to avoid environmental imbalances and destruction of ecosystems. Among the alternatives of biomass for energy purposes forestry, agricultural and urban wastes are highlights. However, raw biomass has low energy efficiency, low density, high humidity, irregular grain, low heating value that restricts their direct use as biofuel. In order to improve the thermal properties and standardize the product is necessary to treat the biomass from industrial processes such as torrefaction and briquetting. In this context, this work aims to analyze and define the potential energy of briquettes of brachiaria grass (Brachiaria ssp.) produced by Briqfeno Industria e Comercio de Feno Ltda located in Tupaciguara - Minas Gerais. The experiments were conducted according to Brazilian rules and the standard product was submitted to density tests, moisture and immediate analysis. A relationship between heating value and moisture content was also defined. Finally, the product was submitted to the torrefaction process that improved its energy and decreased its hygroscopic character when compared to raw briquettes.